A study on planning of yard utilisation for export container in North Butterworth Container Terminal / Md Radzi Mat Nor - Mat Nor, Md Radzi (1996)
North Butterworth Container Terminal as a newly operated container terminal which applies MACH System to control the operation. MACH System or better known as PELKON II is capable to monitor the operation based on real time data. The control and monitoring of operation cover various operating points which include yard operation. Basically the control of yard operation is activated through planning on the forecasted containers to be received. The planning is done by Yard Planning Unit on guide by K9 which is provided by shipping agent. Based on K9, Yard Planning Unit plans for receiving the forecasted containers. The forecasted containers are arranged in the system for the allocation in the yard, based on the segregation of categories, such as Port Of Destination, Vessel Name, Ship Call Number, Sizes, Weight and Types of containers. When the actual containers are received, it will be defined as according to the categories and be arranged for the allocation as specified by the system into the yard address. Author therefore carried out a study to look into the yard operation activities, specifically on the export blocks on how the actual operation reflected against the plans.